Web-based billing application that is used to calculate the cost of internet cafe using the PHP programming language - author author (Jurnal Sistem Informasi, 2005)
Limitation of problems in this paper is the author trying to create a web-based billing application that is used to calculate the cost of internet cafe computer using the PHP programming language for applications, and uses MySQL for the database report. The purpose of this paper is the author trying to create a program that can assist in the process of calculating the cost of rent in cafes and also to help the manufacturing documentation or report transactions using a dynamic database.